'Building Back Better' in Practice : A Science-Policy Framework for a Green Economic Recovery after COVID-19 - Zachariadis, Theodoros; Giannakis, ,Elias; Taliotis, Constantinos; Karmellos, Marios; Fylaktos, Nestor; Howells, Mark; Blyth, Will; Hallegatte, Stephane (World Bank, Washington, DC, 2021)
As humanity’s current production and consumption patterns exceed planetary boundaries, many opinion leaders have stressed the need to adopt green economic stimulus policies in the aftermath of the COVID-19 pandemic, in line with the United Nations Sustainable Development Goals and the Paris Agreement on Climate Change. This paper provides an integrated framework to design an economic recovery strategy aligned with sustainability objectives through a multi-criterion, multi-stakeholder lens. The aim is to enable decisions by policy makers with the aid of transparent workflows that include expert evidence that is based on quantitative open-source modeling, and qualitative input by diverse social actors in a participatory approach. The paper employs an energy systems model and an economic input-output model to provide quantitative evidence and design a multi-criteria decision process that engages stakeholders from government, enterprises, and civil society. As a case study, the paper studies 13 green recovery measures that are relevant for Cyprus and assesses their appropriateness for criteria related to environmental sustainability, socioeconomic and job impact, and climate resilience. The results highlight trade-offs between immediate and long-run effects, between economic and environmental objectives, and between expert evidence and societal priorities. Importantly, the paper finds that a “return-to-normal” economic stimulus is not only environmentally unsustainable, but also economically inferior to most green recovery schemes.